1995
DOI: 10.1016/0735-1097(95)80008-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis with recombinant unglycosylated single-chain urokinase-type plasminogen activator (saruplase) in acute myocardial infarction: influence of heparin on early patency rate (LIMITS study)

Abstract: In acute myocardial infarction, the administration of a heparin bolus before thrombolytic therapy with saruplase is associated with a significantly higher patency at angiography 6 to 12 h after the start of thrombolysis without any appreciable increase in risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…After review of abstracts, an additional 16 studies were excluded. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] After review of the full article, an additional 8 studies were excluded because they were not properly randomized (nϭ3) [33][34][35] ; because at least 1 randomized treatment group did not receive aspirin (nϭ3) 36 -38 ; or because they were preliminary reports or the results of a substudy with the main results having been reported elsewhere (nϭ2). 39,40 Clinical outcome data could not be obtained for 1 additional study, 41 leaving 14 randomized trials, involving a combined total of 25 280 patients, for inclusion in the meta-analysis (Tables 1 to 3).…”
Section: Study Selectionmentioning
confidence: 99%
“…After review of abstracts, an additional 16 studies were excluded. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] After review of the full article, an additional 8 studies were excluded because they were not properly randomized (nϭ3) [33][34][35] ; because at least 1 randomized treatment group did not receive aspirin (nϭ3) 36 -38 ; or because they were preliminary reports or the results of a substudy with the main results having been reported elsewhere (nϭ2). 39,40 Clinical outcome data could not be obtained for 1 additional study, 41 leaving 14 randomized trials, involving a combined total of 25 280 patients, for inclusion in the meta-analysis (Tables 1 to 3).…”
Section: Study Selectionmentioning
confidence: 99%
“…22 The thrombolytic effect is enhanced by heparin, possibly through neutralization of thrombin or by stimulating tPA from the endothelium. 23,24 Prourokinase was utilized for IA thrombolysis studies in the mid-1990s. The Prolyse in Acute Cerebral Thromboembolism (PROACT) trial evaluated IA infusion of prourokinase (6 mg) vs placebo for treatment of middle cerebral artery (MCA) occlusion in patients who presented within 6 hours of symptom onset.…”
mentioning
confidence: 99%
“…heparin. The thrombolytic effect of r-proUK is increased by heparin, possibly through thrombin neutralization or by stimulating tPA release from the endothelium [20,21]. Heparin strongly influenced both recanalization and intracerebral hemorrhage: high rates of partial or complete recanalization were achieved with r-proUK treatment (particularly in those patients receiving higher doses of heparin), although with a higher but not significant rate of intracerebral hemorrhages (15% vs. 7%).…”
Section: Intraarterial Thrombolysismentioning
confidence: 98%